Molecular Mechanisms of Differentiation of Murine Pro-Inflammatory γδ T Cell Subsets - Silva-Santos, Bruno; Serre, Karine (Frontiers in Immunology, 2013)
Gamma-delta (gd) T cells are unconventional innate-like lymphocytes that actively participate in protective immunity against tumors and infectious organisms including bacteria, viruses and parasites. However, gd T cells are also involved in the development of inflammatory and autoimmune diseases. gd T cells are functionally characterized by very rapid production of pro-inflammatory cytokines, while also impacting on (slower but long-lasting) adaptive immune responses. This makes it crucial to understand the molecular mechanisms that regulate  T cell effector functions. Although they share many similarities with ab T cells, our knowledge of the molecular pathways that control effector functions in gd T cells still lags significantly behind. In this review, we focus on the segregation of interferon-gamma versus interleukin-17 production in murine thymic-derived gd T cell subsets defined by CD27 and CCR6 expression levels. We summarize the most recent studies that disclose the specific epigenetic and transcriptional mechanisms that govern the stability or plasticity of discrete pro-inflammatory gd T cell subsets, whose manipulation may be valuable for regulating (auto)immune responses.